Sclerosing Mesenteritis Mimicking Ovarian Tumor: A Very Rare Case - Eşim Büyükbayrak, Esra; Karageyim Karşıdağ, Ayşe Yasemin; Kars, Bülent; Özyapı Alper, Ayşe Gül; Pirimoğlu, Meltem; Kayahan, Sibel; Turan, Cem (Gynecology Obstetrics & Reproductive Medicine, 2011)
Sclerosing mesenteritis is a rare, benign and chronic inflammatory disease with fibrosis that affects the mesentery and on rare occasions mesocolon, peripancreatic region, omentum, retroperitoneum, pelvis. Since the sclerosing mesenteritis has no special clinical manifestations and typical signs, the patients are very easy to be misdiagnosed. We report a case of sclerosing mesenteritis in 38 year-old patient which is misdiagnosed as ovarian tumor both clinically and radiologically. Definitive diagnosis was made with omental biopsy taken via laparatomy. There was only omental involvement without mesenteric and/or intestinal involvement. This is the first case in the literature with primary omental involvement. The striking point of the case was omental replacement towards pelvis mimicking adnexal mass. Even it is a very rare condition sclerosing mesenteritis should be kept in mind in the differential diagnosis of a pelvic mass.